Workshop Revitalisasi Pelaksanaan Bimbingan dan Konseling di SDN 1 Kekeri - A. Hari Witono; I Ketut Widiade; Heri Hadi Saputra; Awal N. K. Rosyidah; Baiq Niswatul Khair; Heri Setiawan (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2024)
Many elementary school teachers have not implemented BK in the classroom. On average, this is because teachers have not yet honed their abilities in implementing guidance and counseling in elementary schools. There are not many self-development activities or training regarding the implementation of BK in elementary schools. The same thing was also found during research at SDN 1 Kekeri. Based on this fact, the Mataram University service team took the initiative to hold a workshop on revitalizing the implementation of Guidance and Counseling in elementary schools. One of the main tasks of the tri dharma of higher education is to serve. The form of activity chosen was a workshop on strengthening the role of elementary school teachers as counselors as well as strengthening the implementation of BK in elementary schools. To achieve the objectives of counseling and training as implied in the title of this community service, several methods are used, namely lectures, questions and answers or discussions and mentoring. The result of the service is a workshop held at partner elementary schools on Friday, June 16 2023 at 09.00-12.00 WITA. The participants were 13 teachers and 1 principal of SDN 1 Kekeri. The workshop was divided into 3 sessions, namely opening, presentation of material, and questions and answers. The material presented is: (1) the concept of guidance and counseling; (2) the scope of BK in elementary school; (3) the form of guidance and counseling services in elementary schools; (4) BK management in elementary schools; and (5) challenges and supports for implementing BK in elementary schools. The activity went smoothly and the initial aim was to increase the understanding of teachers at SDN 1 Kekeri regarding the implementation of guidance and counseling services in elementary schools.